Somatic Mosaic Pathogenic Variant Gradient Detected in Trace Brain Tissue From Stereo-EEG Depth Electrodes. (6th December 2022) - Ye, Zimeng; Bennett, Mark F.; Neal, Andrew; Laing, Joshua A.; Hunn, Martin K.; Wittayacharoenpong, Thanomporn; Todaro, Marian; Patel, Sheila K.; Bahlo, Melanie; Kwan, Patrick; O'Brien, Terence J.; Scheffer, Ingrid E.; et al.
Abstract : Background and Objectives: Mosaic pathogenic variants restricted to the brain are increasingly recognized as a cause of focal epilepsies. We aimed to identify a mosaic pathogenic variant and its anatomical gradient in brain DNA derived from trace tissue on explanted stereoelectroencephalography (SEEG) electrodes. Methods: We studied a patient with nonlesional multifocal epilepsy undergoing presurgical evaluation with SEEG. After explantation, the electrodes were divided into 3 pools based on their brain location (right posterior quadrant, left posterior quadrant, hippocampus/temporal neocortex). Tissue from each pool was processed for trace DNA that was whole genome amplified prior to high-depth exome sequencing. Droplet digital PCR was performed to quantify mosaicism. A brain-specific glial fibrillary acidic protein (GFAP) assay enabled cell-of-origin analysis. Results: We demonstrated a mosaic gradient for a novel pathogenic KCNT1 loss-of-function variant (c.530G>A, p.W177X) predicted to lead to nonsense-mediated decay. Strikingly, the mosaic gradient correlated strongly with the SEEG findings because the highest variant allele frequency was in the right posterior quadrant, reflecting the most epileptogenic region on EEG studies. An elevated GFAP level indicated enrichment of brain-derived cells in SEEG cell suspension. Discussion: This study demonstrates a proof of concept that mosaic gradients of pathogenic variants can be established using trace tissue from explanted SEEG electrodes.